Estudo Químico de Croton floribundus Spreng (Euphorbiaceae) - Uchôa, Paula Karina Santos (2011)
The present work reports the chemical study of root barks from Croton floribundus Spreng, collected at Pacoti-CE. The phytochemical investigation of hexane extract lead to the isolation of three kaurene-type diterpenes, ent-kaur-16-en-19-oic acid, ent-kaur-16-en-6,19-diol and ent-16-hydroxykaur-11-en-19-oic acid, reported for the first time to the genus Croton. In addition, four trachylobane-type diterpenes were isolated and identified as ent-trachyloban-19-oic acid, ent-15-hydroxytrachyloban-19-oic acid, ent-trachyloban-19-ol and the ent-trachyloban-18,19-diol, which was described as a new compound. Two derivatives of ent-trachyloban-18,19-diol were prepared through acetylation and oxidation reactions, and were characterized as ent-18,19-diacetoxytrachylobane and ent-18-nortrachyloban-19-oic acid. Each of these isolated diterpenes were submited to cytotoxic activity using colon (HCT-8), breast (MDAMB-435) and brain (SF-295) cell lines, and the compounds ent-caur-16-en-6,19-diol and ent-18-nortrachyloban-19-oic acid showed moderated activity in preliminaries assays. The secondary metabolites were isolated through usual chromatography techniques, using thin layer chromatography, column chromatography and high performance liquid chromatography. The structure determination of the isolated compounds was performed through physical (melting point and optical rotation) and spectrometrical techniques, such as: infrared (IR), mass spectrometric (MS) and nuclear magnetic resonance (NMR), including bidimensional experiments, and comparison with the literature data.